Migration Processes and Self-Rated Health among Marriage Migrants in South Korea - Chang, Hsin-Chieh (Ethn Health, 2015)
BACKGROUND: Research on migrant health mostly examines labor migrants, with some attention paid to the trauma faced by refugees. Marriage migrants represent an understudied vulnerable population in the migration and health literature. OBJECTIVES: Drawing on a Social Determinants of Health (SDH) approach, we use a large Korean national survey and stratified multivariate regressions to examine the link between migration processes and the self-rated health of Korea’s three largest ethnic groups of marriage migrants: Korean-Chinese, Vietnamese, and Han Chinese. RESULTS: We find that post-migration socioeconomic status and several social integration factors are associated with the health of marriage migrants of all three groups. Specifically, having more social relationships with Koreans is associated with good health among marriage migrants, while having more social relationships with co-ethnics is associated with worse health. Marriage migrants’ perceived social status of their natal and marital families is a better predictor of their health than more objective measures such as their education attainment and that of their Korean husbands. The post-migration social gradients among all ethnic groups demonstrate a dose-response effect of marital family’s social standing on marriage migrants’ health, independent of their own education and the social standing of their natal families. Lastly, we find some ethnicity-specific predictors such as the association between higher educational level and worse health status among the Vietnamese. This variability by group suggests a more complex set of social determinants of health occurred during the marriage migration processes than a basic SDH framework would predict. CONCLUSION: Using a new immigrant destination, South Korea, as an example, we conclude that, migration and health policies that reduce ethnicity-specific barriers and offer integration programs in early post-migration stages may offer a pathway to good health among marriage migrants.